Jerusalem : history of a global city - Lemire, Vincent, 1973-; Berthelot, Katell; Loiseau, Julien; Potin, Yann; Froggatt, Juliana, 1981- (University of California Press, 2022)
"An expansive history of Jerusalem as a cultural crossroads, and a fresh look at the urban development of one of the world's most mythologized cities. Jerusalem is often seen as an eternal battlefield in the 'clash of civilizations' and in endless, inevitable wars of religion. But if we abandon this limiting image when reviewing the entirety of its concrete urban history--from its beginnings to today--we discover a global city at the world's crossroads. Jerusalem is the common cradle of Judaism, Christianity, and Islam, whose long and intertwined pasts include as much exchange and reciprocal influence as conflict and confrontation. This synthetic account is the first to make available to the general public Jerusalem's whole history, informed by the latest archaeological finds, unexplored archives, and ongoing research and offering a completely renewed understanding of the city's past and geography. This book is an indispensable guide to understanding why the world converges on Jerusalem"--